Strategies of Extension Service Providers To Meet the Information Needs of the Farmers (SAARC Journal of Agriculture, 2021)
The role of Information Communication and Technology (ICT) is yet to be fully realized to receive its full potential benefits in agricultural information dissemination services. The present study is undertaken to enhance agricultural knowledge and minimize the information gaps between farmers’ needs and new technologies. It reviews recent ICT initiatives in agriculture and farmers access to agricultural information services in Bangladesh. The role of ICT on farmers enhanced agricultural production is also discussed in the paper. The current research proves that agriculture information is not only for libraries, research stations, and national and international agricultural database. Agriculture information services are to be provided by the Government, NGO, private organizations, agricultural research organizations, and advisory centers. The data were collected from questionnaire and interviews and they were coded, decoded, and interpreted in descriptive statistics through tables, graphs, and chart. The findings were arranged in separate sections with respective manners. This study contributes to the field of agricultural information dissemination systems of Bangladesh. It significantly elicits strong relationship between the use of ICT and farmers’ enhanced production led income. It was concluded with recommendations for the information providers, researchers, policy makers, and stakeholders for making extension services more effective.SAARC J. Agric., 19(1): 249-258 (2021)